Penerapan Pemberantasan Tindak Pidana Terorisme Pasal 12A Ayat (2) Undang-undang No. 5 Tahun 2018 Dihubungkan dengan Keadilan bagi Pelaku Terorisme - Prihadiati, R.r. Lyia Aina; Putra, Yudha Handika; Aris, Umar (PT Elaborium Elevasi Indonesia, 2023)
Terrorism is a serious threat to national and international security, Terrorism is acts or threats of violence performed by group, individuals or organization to creates power, cause damage or achieving political goals, ideological, religious, or social. in article 12 paragraph (2) of law no. 5 of 2018 it can be explained that a person who is only a member of a group of banned organizations can be immediately caught by the law and convicted. but in determining the efforts or actions to be taken by law enforcement officers in addition to strong evidence based on article 184 kuhap must also conduct an in-depth analysis or assessment to determine a person's involvement in terrorism networks in order to create benefits and justice in terms of determining the right steps in preventing and enforcing terrorism crimes. promote deradicalization as a preventive measure that can reach down to the grassroots that is not only focused on suspects or convicted terrorists who are sentenced, but this program is aimed at supporters and individuals in the local area who have been exposed to revolutionary thoughts.